Essays on the history of scientific thought in modern Japan - Kanamori, Osamu 1954-; Carr, Christopher (Translator); Sheftall, Mordecai G. (2016)
"This book covers the history of physics, chemistry, and pharmacology in modern Japan, focusing on the 1920s through the early 1960s. Led by the editor's introduction, 'A Portrait of the History of Scientific Thought,' readers will soon find themselves in the middle of a complex double narrative comprising both 'the telling of history' and 'the telling of the history of history.' In the end, readers will come to understand an intricate historical aspect, made possible through such a grand and meta-appreciation"--Back cover.
Introduction A Portrait of the History of Scientific Thought Osamu Kanamori. Section 1. Towards a Chronicle of the History of Scientific Thought Section 2. Prewar Trends Section 3. Study of the History of Science Gains Autonomy Section 4. The Infiltration of "Scientific Politics" and the Disputes Surrounding It -- Chapter 1. Nuclear And Elementary Particle Physics: The Evolution Of A Competitive View Of Science Takuji Okamoto. Section 1. From the Inception of Quantum Mechanics to the Nobel Prize of Hideki Yukawa Section 2. Establishment of a Competitive Scientific View: the Agony of Hantar?o Nagaoka Section 3. The Development of Competition and the Fate of the Competitive View of Science: From the Saturnian Model of the Atom to Anti-Relativity Section 4. The Advent of Quantum Mechanics Section 5. Meson Theory, Cyclotron, New Weapons Section 6. Research on the Atomic Nucleus and Elementary Particles in Defeat Section 7. Supporters of Basic Science -- Chapter 2. The Formation of Japan's Tradition Of Organic Chemistry Research With Rik?o Majima Masanori Kaji. Section 1. In the Beginning: The Promise of the History of Scientific Thought in Twentieth Century Japanese Chemistry Section 2. The History of Japanese Chemistry up to Majima Section 3. Rik?o Majima's Path to Becoming a Chemist Section 4. Rik?o Majima's Research in Germany Section 5. Rik?o Majima's Arrival at T?ohoku Imperial University and the Completion of His Research on Urushiol Section 6. The Further Development of Organic Chemistry Research on Natural Products by Majima's Students in Japan: Expansion and Limitations Section 7. Rik?o Majima's Subsequent Research and Accomplishments, or His Philosophical Pathway as Seen from His Journal Section 8. In Conclusion--Remaining Challenges Facing a History of Thought in Chemistry -- Chapter 3. The Formation And Development Of The Self-Image Of Kamp?o Medicine In Japan: The Relationship Between Showa-Period Kamp?o And Science Shin Chang-Geon. Section 1. Situating the Issue Section 2. The Historical Foundation of Showa Kamp?o Medicine Section 3. The Origin and Self-Image of the "East Asian Medicine" Movement Section 4. Eliminating Korean Influence from the New Oriental Medicine Section 5. Conclusion.
"This book is an English translation of excerpts from 'Showa zenki no kagaku shis?o shi,' published in Japanese by Keiso Shobo Publishing Co., Ltd. in 2011. The English edition comprises Introduction (Osamu Kanamori), Chapter 1 (Takuji Okamoto), Chapter 2 (Masanori Kaji), and Chapter 4 (Shin Chang-Geon) of the Japanese edition"--Title page verso.
Includes bibliographical references (pages 275-314) and indexes.
Keywords: Science -- Japan -- History -- 20th century; Japan -- History; History